PENINGKATAN KETERAMPILAN MENULIS NASKAH DRAMA MELALUI FILM PENDEK “JALAN PULANG” SISWA KELAS XI SMA NEGERI 1 PENANGGALAN - Zulfikar; Pohan, Jusrin; Sari, Sartika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the drama scriptwriting skills of students in class XI IPA 1 at SMAN 1 Penanggalan, Kota Subulussalam, Aceh, by utilizing short film media. The classroom action research was conducted at SMAN 1 Penanggalan, Kota Subulussalam, Aceh, specifically in class XI IPA 1. The study was carried out over three months, from August to October 2024. The research data consisted of interview results, test results, and observation sheets obtained from interviews, test implementation, and observations. The test results in the first cycle showed that the percentage of students who scored above the Minimum Competency Criterion (KKM) was only 63.33% of the total students in class XI. In other words, the test results in the first cycle indicated an improvement in student achievement from the pre-action stage, increasing from 33.33% to 63.33%. However, the test results in the first cycle did not reach the target of 75% of students scoring above the KKM. These results indicated the need for a second cycle to further enhance students' drama scriptwriting abilities. Subsequently, it was found that the percentage of students scoring above the KKM in the second cycle increased to 83.33% of the total students in class XI. In other words, the test results in the second cycle showed an improvement in student achievement from the first cycle, increasing from 63.33% to 83.33%. The test results in the second cycle exceeded the target of 75% of students scoring above the KKM.